A jogi személyiség kérdése az erdélyi római katolikus státust illetően az 1932-es emlékirat tükrében - Sarnyai, Csaba Máté (Közép-Európai Közlemények, 2010)
In 1932 the Governing body of the Transylvanian Roman Catholic Status (Council) turned to the Rumanian government with a memorandum. We intend to present and analyse those passages of this document which affect the legal status of the institution, because those parts were seriously attacked by the anti-Hungarian circles of Rumania. Through this we can demonstrate how after the change of empire Hungarians tried to defend their institution, which was considered to be one of the oldest ones and one which essentially influenced Hungarian-Catholic identity, from the increasing Rumanian elimination efforts. Prior to this, as an introduction we present some moments from the era in order to outline the situation of the Transylvanian Catholic Church. Finally, we present the effect of the efforts formulated in the memorandum or rather their unrealization.